Drug offenders in the global criminal justice system - VanHorne, Sheryl (HEUNI papers, 1999)
The present work assesses the extent, variation and changes in drug trafficking, drug possession and all drug offences in criminal justice systems around the world between. Across the five years of study there was a strong international trend over time, showing relatively small but widespread increases in drug offenders for each stage from suspects arrested by law enforcement, through prosecutions and convictions, to prison admissions. The international mean for all drug offences as a percentage of all offences was 7% of suspects, 7% of prosecutions, 6% of convictions, and 11% of prison admissions in the most recent year for which data was available. The non-parametric sign-test is used to show that the international trends were statistically significant in terms of the number of countries increasing or decreasing the proportion of drug offenders. It seems that, in general, criminal justice systems around the world are characterised more by the similarities than differences in the proportions of drug offenders at different stages. However, several statistically deviant countries are identifiable at different criminal justice stages and at different times. Some specific issues are worthy of further examination. In particular there is the possibility that the United States is not particularly more punitive at sentencing or imprisonment than other countries when it comes to drug offenders, but rather, that it has a relatively greater tendency to prosecute drug offences cases. Further, at the stage of imprisonment, drug offenders constitute a larger proportion of all offenders imprisoned in Belgium, Italy and Germany, than they do in the United States. Although people are often quick to identify the US the world's penal sadist when it comes to drug offenders, the present data set suggests that for the early 1990's at least, there is no conclusive evidence that this is the case. The further investigation of these and other issues may provide information of relevance to drug policy or criminal justice policy at the national or international level. Variations in sentence lengths for drug offences are also examined, although the data is more fragmented. For those countries that responded, the international median sentence length for possession offences is around one year compared to somewhere between three and five years for trafficking. The findings and their interpretation should be viewed with caution due to the limitations of the data. However, the analysis suggests that the United Nations crime survey has been under-utilised as a means of developing knowledge and information of relevance to national and international drug policy and criminal justice policy. A range of possibilities for furthering the present work is suggested.